On the Welfare Implications of Automation - Eden, Maya (World Bank, Washington, DC, 2015)
This paper establishes that the rise in the income share of information and communication technology accounts for half of the decline in labor income share in the United States. This decline can be decomposed into a sharp decline in the income share of “routine” labor—which is relatively more prone to automation—and a milder rise in the non-routine share. Quantitatively, this decomposition suggests large effects of information and communication technology on the income distribution within labor, but only moderate effects on the distribution of income between capital and labor. A production structure calibrated to match these trends suggests modest aggregate welfare gains from automation.